2022
DOI: 10.3389/fpls.2022.906751
|View full text |Cite
|
Sign up to set email alerts
|

Automatic and Accurate Acquisition of Stem-Related Phenotypes of Mature Soybean Based on Deep Learning and Directed Search Algorithms

Abstract: The stem-related phenotype of mature stage soybean is important in soybean material selection. How to improve on traditional manual methods and obtain the stem-related phenotype of soybean more quickly and accurately is a problem faced by producers. With the development of smart agriculture, many scientists have explored soybean phenotypes and proposed new acquisition methods, but soybean mature stem-related phenotype studies are relatively scarce. In this study, we used a deep learning method within the convo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…It is important to emphasize, however, that the high classification accuracies are almost always obtained on data with rather limited variability, so the reported results are not necessarily valid for real practical conditions (this issue is addressed in more depth in the next section). Disease recognition RGB DenseNet201 0.97 1 [23] Water stress detection RGB AlexNet, GoogLeNet, Inception V3 0.93 1 [24] Root phenotyping RGB CAE 0.66-0.99 [15] Weed detection RGB JULE, DeepCluster 0.97 1 [11] Volunteer corn detection RGB, CIR GoogleNet 0.99 1 [25] Disease severity RGB FPN, U-Net, DeepLabv3+ 0.95-0.98 [3] Pest detection HS Attention-ResNet 0.95 1 [26] Stem phenotyping RGB YOLO X 0.94 1 [27] Pod detection, yield prediction RGB YOLO v5 0.94 4 [28] Disease recognition RGB DCNN 0.98 1 [29] Seed counting RGB Two-column CNN 0.82-0.94 [30] Pest detection RGB Modified YOLO v4 0.87 2 [31] Disease severity RGB RetinaNet 0.64-0.65 1,2 [32] Weed detection RGB Faster R-CNN, YOLO v3 0.89-0.98 [19] Defoliation estimation RGB, synthetic AlexNet, VGGNet and ResNet 0.98 3 [33] Disease recognition RGB DIM-U-Net, SR-AE, LSTM 0.99 2 [34] Weed detection RGB DCNN 0.93 1 [35] Pest detection RGB Several CNNs 0.94 1 [12] Seed-per-pot estimation RGB DCNN 0.86 1 [36] Cultivar identification RGB ResNet-50, DenseNet-121, DenseNet 0.84 1 [37] Disease recognition RGB AlexNet, GoogLeNet, ResNet-50 0.94 1 [38] Pod counting RGB YOLO POD 0.97 4 [39] Seed phenotyping RGB, synthetic Mask R-CNN 0.84-0.90 [40] Yield prediction, biomass HS DCNN 0.76-0.91 [41] Disease recognition RGB GAN 0.96 1 [42] Disease recognition RGB Faster R-CNN 0.83 5 [43] Weed detection RGB Faster R-CNN 0.99 1 [44] Pod counting RGB R-CNN, YOLO v3, YOLO v4, YOLO X 0.90-0.98 [45] Seed defect recognition RGB MobileNet V2 0.98 1 [46] Seed counting RGB P2PNet-Soy 0.87 4 [47] Cultivar identification HS DCNN 0.90 1 …”
Section: Proximal Images As Main Input Datamentioning
confidence: 99%
“…It is important to emphasize, however, that the high classification accuracies are almost always obtained on data with rather limited variability, so the reported results are not necessarily valid for real practical conditions (this issue is addressed in more depth in the next section). Disease recognition RGB DenseNet201 0.97 1 [23] Water stress detection RGB AlexNet, GoogLeNet, Inception V3 0.93 1 [24] Root phenotyping RGB CAE 0.66-0.99 [15] Weed detection RGB JULE, DeepCluster 0.97 1 [11] Volunteer corn detection RGB, CIR GoogleNet 0.99 1 [25] Disease severity RGB FPN, U-Net, DeepLabv3+ 0.95-0.98 [3] Pest detection HS Attention-ResNet 0.95 1 [26] Stem phenotyping RGB YOLO X 0.94 1 [27] Pod detection, yield prediction RGB YOLO v5 0.94 4 [28] Disease recognition RGB DCNN 0.98 1 [29] Seed counting RGB Two-column CNN 0.82-0.94 [30] Pest detection RGB Modified YOLO v4 0.87 2 [31] Disease severity RGB RetinaNet 0.64-0.65 1,2 [32] Weed detection RGB Faster R-CNN, YOLO v3 0.89-0.98 [19] Defoliation estimation RGB, synthetic AlexNet, VGGNet and ResNet 0.98 3 [33] Disease recognition RGB DIM-U-Net, SR-AE, LSTM 0.99 2 [34] Weed detection RGB DCNN 0.93 1 [35] Pest detection RGB Several CNNs 0.94 1 [12] Seed-per-pot estimation RGB DCNN 0.86 1 [36] Cultivar identification RGB ResNet-50, DenseNet-121, DenseNet 0.84 1 [37] Disease recognition RGB AlexNet, GoogLeNet, ResNet-50 0.94 1 [38] Pod counting RGB YOLO POD 0.97 4 [39] Seed phenotyping RGB, synthetic Mask R-CNN 0.84-0.90 [40] Yield prediction, biomass HS DCNN 0.76-0.91 [41] Disease recognition RGB GAN 0.96 1 [42] Disease recognition RGB Faster R-CNN 0.83 5 [43] Weed detection RGB Faster R-CNN 0.99 1 [44] Pod counting RGB R-CNN, YOLO v3, YOLO v4, YOLO X 0.90-0.98 [45] Seed defect recognition RGB MobileNet V2 0.98 1 [46] Seed counting RGB P2PNet-Soy 0.87 4 [47] Cultivar identification HS DCNN 0.90 1 …”
Section: Proximal Images As Main Input Datamentioning
confidence: 99%
“…In recent years, with the development of computer vision and deep learning techniques, image-based methods for measuring plant phenotypic traits have received widespread attention and application. Image sensors collect image information of plants, such as RGB cameras [5][6][7][8][9], depth cameras [10][11][12][13], and optical spectrometers [14,15], which are then analyzed and processed with deep learning models to facilitate the automated, precise, and intelligent measurement of plant phenotypic traits. Li et al [16] used UAV multispectral data as input to predict winter wheat yield, the convolutional neural network (CNN) model gave the best results, with R 2 of 0.752 and NMSE of 0.404 t•ha −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that transfer learning based on the VGG19 model achieved the highest accuracy for both crops. Guo et al [5] used a deep learning method coupled with a novel directed search algorithm to obtain stem-related phenotypes for soybeans. The Pearson correlation coefficients (R) of plant height, pitch number, internodal length, main stem length, stem curvature, and branching angle were 0.9904, 0.9853, 0.9861, 0.9925, 0.9084, and 0.9391, respectively.…”
Section: Introductionmentioning
confidence: 99%